Brief Report: Improving Early Infant Diagnosis Observations. (1st March 2020) - Webb, Karen; Chitiyo, Vivian; Mahachi, Nyikadzino; Huruva Mukungunugwa, Solomon; Mushavi, Angela; Zizhou, Simukai; Engelsmann, Barbara; Abbas Ferrand, Rashida; Neuman, Melissa; Hartogensis, Wendy; Geng, Elvin
Abstract : Background: Improving efforts toward elimination of mother-to-child transmission of HIV requires timely early infant diagnosis (EID) among all HIV-exposed infants, but the occurrence of timely EID and infant survival may be underascertained in routine, facility-bound program data. Methods: From March 2015 to May 2015, we traced a random sample of HIV-positive mother and HIV-exposed infant pairs lost to follow-up for EID in facility registers in Zimbabwe. We incorporated updated information into weighted survival analyses to estimate incidence of EID and death. Reasons for no EID were surveyed from caregivers. Results: Among 2651 HIV-positive women attending antenatal care, 1823 (68.8%) infants had no documented EID by 3 months of age. Among a random sample of 643 (35.3%) HIV-exposed infants lost to follow-up for EID, vital status was ascertained among 371 (57.7%) and updated care status obtained from 256 (39.8%) mothers traced. Among all HIV-infected mother–HIV-exposed infant pairs, weighted estimates found cumulative incidence of infant death by 90 days of 3.9% (95% confidence interval: 3.4% to 4.4%). Cumulative incidence of timely EID with death as a competing risk was 60%. The most frequently cited reasons for failure to uptake EID were "my child died" and "I didn't know I should have my child tested." Conclusions: Our findings indicate uptake of timely EID among HIV-exposed infants is underestimated in routine health information systems. High, early mortality among HIV-exposed infants underscores the need to more effectively identify HIV-positive mother–HIV exposed infant pairs at high risk of adverse outcomes and loss to follow-up for enhanced interventions.